Measurement of ϒ production in pp collisions at √s = 2.76 TeV - Aaij, Roel; Bachmann, Sebastian; Bien, Alexander; De Cian, Michel; Di Canto, Angelo; Dordei, Francesca; Esen, Sevda; Färber, Christian; Gersabeck, Evelina; Grillo, Lucia; Hansmann-Menzemer, Stephanie; Jäger, Andreas; et al. (The European physical journal. C, Particles and fields, 2014)
The production of ϒ(1S), ϒ(2S) and ϒ(3S) mesons decaying into the dimuon final state is studied with the LHCb detector using a data sample corresponding to an integrated luminosity of 3.3pb−1 collected in proton–proton collisions at a centre-of-mass energy of √s = 2.76TeV
Im Titel wird das griechische Zeichen für Ypsilon verwendet
The LHCb Collaboration: R. Aaij, B. Adeva, M. Adinolfi, A. Affolder, Z. Ajaltouni, J. Albrecht, F. Alessio, M. Alexander, S. Ali, G. Alkhazov [und 673 weitere]
Gesehen am 18.09.2020